Hak-Hak yang Memberi Jaminan dalam Prespektif Hukum Positif dan Hukum Islam: Analisis Perbandingan - Zeinaful Jannah; Siti Solifah; Akmalurrozi Akmalurrozi; Ahmad Musadad; Yusuf Maulana Imron (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2025)
This article aims to analyze and compare the concept of rights that provide guarantees from the perspectives of positive law and Islamic law, as well as to examine the potential for integrating both within the framework of a plural national legal system. The methodology used is qualitative library research with a normative approach, utilizing primary sources such as statutory regulations and classical and contemporary Islamic jurisprudence literature, along with secondary sources including scholarly journals and books published within the last ten years. The results of the study indicate that both legal systems equally recognize the importance of guarantee rights as instruments of justice and legal certainty, albeit through different approaches: positive law emphasizes juridical-administrative aspects, while Islamic law highlights moral values and social responsibility. Although there is potential for harmonious integration, implementation still faces structural and cultural challenges, thereby necessitating institutional reform and capacity building within society to realize a fair and adaptive legal system in the context of national legal pluralism.